Nahwu Learning Through Banjar Culture with Syahid Table in South Kalimantan - Rafiatun Najah Qomariah; Akhmad Muzakki; Umi Machmudah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
The purpose of this study were to reveal the cultural aspects of Nahwu learning at Islamic Boarding School, South Kalimantan. This research was case study research with a qualitative approach carried out at Darul Ilmi Islamic Boarding School for Girl, South Kalimantan. The results of this study showed the cultural aspects of Nahwu learning at Islamic Boarding School, South Kalimantan, were: - The use of Banjarese Malay in explaining the Nahwu rules, the strategy of the Syahid, the explanation of the Syahid and the translation of the characteristics of Banjar, - the Syahid in the Banjarese language in the form of a concept a graphic image table consisting of Syahid, kalimat, alamat, hukum, mahal, liys tengah, a’mil, alamat and liys akhir, where each table contains sentence functions from examples related to the topic being studied. - translation of banjar characteristics include: “Bermula” the marker for “مبتدأ”, “yaitu” the marker for “خبر”, “ulih” the marker for “فاعل”, “akan” the marker for “مفعول” The affix “nya” ​​the marker for “إضافة”, “hal keadaan” the marker for “حال”, and “berbilang” of markers for “جمع”. This study indicated that nahwu learning based on regional culture by combining concept learning conditions and the use of the mother tongue contributes to facilitating and helping students' difficulties in learning Nahwu.